Relationship between the mechanical properties of epoxy/PMMA-b-PnBA-b-PMMA block copolymer blends and their three-dimensional nanostructures - H. Kishi (eXPRESS Polymer Letters, 2017)
Nanostructures of diglycidyl ether of bisphenol-A epoxy/poly(methyl methacrylate)-b-poly(n-butyl acrylate)-b-poly(methyl methacrylate) (PMMA-b-PnBA-b-PMMA) triblock copolymer (BCP) blends were studied in relation to their mechanical properties. Three types of self-assembled nanostructures, such as spheres, random cylinders, and curved lamella, were controlled in phenol novolac-cured epoxy blends with a wide range of BCP content. Three types of nanostructures were observed using two-dimensional and three-dimensional transmission electron microscopy (TEM). The 3D-TEM, dynamic viscoelastic analyses, and theoretical model on the elastic modulus clarified that the spheres and the random cylinders, consisted of epoxy-immiscible PnBA phases, were discontinuously dispersed in the epoxy matrix. In contrast, the curved lamella formed co-continuous nanostructure, in which both the PnBA and epoxy phases formed continuous channels. The fracture toughness (critical strain energy release rate, GIC) and the flexural moduli of elasticity (E) of the cured blends were evaluated for various amounts of BCP content. The highest GIC was obtained from the random cylindrical nanostructured blends in the three types of nanostructures with the same PnBA content. The lowest E was obtained for the curved lamella with co-continuous nanostructures. The details of deformation and fracture events were observed using optical and electron microscopy, and the mechanical properties are discussed in relation to the nanostructures.